(3cJGH aj WHGFY GdEfSGf hGdMjhGf hGdMTQGJ hGdWjQ hGdCSeGcs
(3ChdgG (B:s
(3aGdcdeI cf hHgPg GdcdeI UGQ GdJQGH GdeJaQb GdCLRGA MSOkG edJekG s
(3BNQgG (B:s
(3hPdc Cfge EPG HQRhG ef GdHMQ Edi GdHQ jJfSehf ajbY Hge GdUjGOhf aEPG HchG QMeghge hCWdbghge BNQ GdcJGH hGddg Gdehab ddUhGH s
(3jfbd GdeDda Yf hehab GdOjf YHO GddWja GdHZOGOi GdeJhai ai SfI (B629 (3QJHg GdeDda Ydi JSYI CHhGHs
(3ZGdH GdUaMGJ GdJi Ydi GdjSGQ egRhRI ai GdJUhjQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B142 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs